Analysis of the effect of annealing rate on the thinness film of BaZr0.4Ti 0.6O3 at 800°C for 2 hours - Tengku Said Hussain Shahab; Yanuar Hamzah; Zulkarnain Krisman; Ari Sulistyo Rini; Rahmi Dewi (Journal of Aceh Physics Society, 2021)
Abstrak. Ferroelektrik merupakan bahan yang mempunyai polarisasi spontan serta mempunyai kemampuan mengubah polarisasi internalnya dengan menggunakan medan listrik yang sesuai. Ferroelektrik juga diaplikasikan sebagai kapasitor. Material ferroelektrik buat dalam bentuk film tipis. Barium Zirconium Titanate (BZT) dengan komposisi BaZr0.4Ti0.6O3 dibuat menggunakan metode sol-gel. Substrat yang digunakan yaitu FTO yang telah di etching dan di lapisi BZT serta di annealing pada suhu 800°C selama 2 jam dengan kenaikan laju suhu annealing yaitu 5°C dan 10°C. Sampel di karakterisasi menggunakan XRD. Hasil karakterisasi XRD menunjukkan adanya puncak-puncak yang menandakan terdapat struktur kristal. Struktur kristal yang dihasilkan berada pada bidang 100  pada sudut 2θ = 22.78°, bidang 110  pada sudut 2θ = 32.17°, bidang 111 pada sudut 2θ = 38.42°, bidang 200 pada sudut 2θ = 47.73°. Struktur yang dihasilkan pada penelitian ini yaitu tetragonal dimana a = b = 3.91 nm dan c = 4.05 nm. Laju kenaikan suhu berpengaruh pada puncak Difraksi Sinar-X. Nilai FWHM untuk 5°C lebih kecil dari 10°C, ini menunjukan adanya kerapatan yang lebih besar saat di annealing dengan laju 5°C. Nilai ukuran kristal yang di dapat dengan kenaikan suhu 5°C dan 10°C pada bidang 100 yaitu 3.94 nm dan 3.22 nm. Ukuran kristal berbanding terbalik dengan nilai FWHM dimana laju kenaikan suhu annealing yang kecil menyebabkan ukuran kristal membesar. Abstract Ferroelectrics is a material that has spontaneous polarization and ability to change its internal polarization by using a suitable electric field. Ferroelectricsis also applied as a capacitor. The ferroelectric material is made in the form of a thin film. Barium Zirconium Titanate (BZT) with the composition BaZr0.4Ti 0.6O3 is prepared using the sol-gel method. The substrate used is FTO which has been etched and coated with BZT and annealed at a temperature of 800°C for 2 hours with a increase in the annealing temperature speed of 5°C and 10°C.Samples are characterized using XRD. The XRD characterization results show peaks indicating a crystal structure. The resulting crystal structure is in a plane 100 at an angle of 2θ = 22.78°, a plane 110 at an angle of 2θ = 32.17°, a plane 111 at an angle of 2θ = 38.42°, a plane 200 at an angle of 2θ = 47.73°. The resulting structure in this study is a tetragonal where a = b = 3.91 nm  and c = 4.05 nm. The speed at which temperature increases has an effect on the peak of the X-Ray Diffraction.The FWHM value for 5°C is less than 10°C which indicates a greater density when annealed at a speed of 5 °C. The value of the crystal size obtained with an increase in temperature of 5°C and 10°C in the  plane 100 is 3.94 nm and 3.22 nm. The crystal size is inversely proportional to the FWHM value where the small speed of the annealing temperature increase causes the crystal size to enlarge.Keywords: BaZr0.4Ti0.6O3 Thin Film,  Speed of Annealing Temperature Increase,  Sol-gel method, X-Ray Diffraction (XRD).